ANALISIS KESEDIAAN MEMBAYAR (WILLINGNESS TO PAY) BUAH-BUAHAN PADA RUMAH TANGGA DI KELURAHAN CIMUNING, KECAMATAN MUSTIKA JAYA, KOTA BEKASI SAAT PANDEMI COVID-19 - Dhifa Prilia Purnomo; Trisna Insan Noor; Eliana Wulandari; Lucyana Trimo (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2022)
Covid-19 is an outbreak that originated in Wuhan, China and spread to Indonesia. The spread of Covid-19 in Indonesia is happening so fast and the development of positive cases in Indonesia is increasing every day until 2021. The Indonesian Ministry of Health recommends several fruits to meet nutritional intake during the Covid-19 pandemic, namely watermelon, apples, strawberries, red grapes, bananas, oranges. , papaya, mango, pineapple, poor apple, green grapes, melon, avocado and mangosteen. One of the areas in West Java is RW 10 Cimuning Village, Mustika Jaya District, Bekasi City. The area is one of the areas where several residents have contracted Covid-19. Circumstances like this have made households in these areas have considerations between health that must always be maintained and household income which is the impact of the Covid-19 pandemic. This study aims to describe the characteristics of households that buy fruits during the Covid-19 pandemic, what value households are willing to pay for fruits during the Covid-19 pandemic and what factors affect the value of their willingness to pay for fruits. household during the Covid-19 pandemic. This study uses a quantitative design and survey method using a questionnaire. The analysis used is instrument test, descriptive statistical analysis, contingent valuation method, Likert scale and multiple linier regression analysis. The results showed the average value of Willingness To Pay for fruits by households in RW 10, Kel. Cimuning, Kec. Mustika Jaya, Bekasi City varies greatly with each type of fruit. The fruit with the highest average WTP value was green grapes with a value of Rp. 83,000/kg and the fruit with the lowest average WTP value was papaya with a value of Rp. 17,000/kg. The factors that influence the household's willingness to pay for fruits during the Covid-19 pandemic are the health impact, the number of family members and the price of the product.